Significance of Labor Productivity and Labor Cost on Foreign Direct Investment: Evidence from Bangladeshi Textile Sector (Global Journal of Management and Business Research, 2023)
Foreign direct investment (FDI) is vital in boosting industrial and economic growth, particularly in developing countries, including Bangladesh. During the last two decades, Bangladesh received a significant amount of FDI in the textile industry, while it has emerged as a major textile exporter with high economic growth. The empirical evidence shows that the availability of a skilled labor force, low labor cost, and favorable investment climate in the host country are the critical determinants of FDI inflows into the manufacturing sectors. This study intends to investigate the impact of labor productivity and labor costs on FDI inflows in the Bangladeshi textile industry. Using the ordinary least square (OLS) regression model, 30-year time series data of the variables were analyzed. The study found that FDI inflows in the Bangladeshi textile sector are significantly determined by labor cost, labor productivity, infrastructure, market growth, and market size. The study results have significant implications for the policymakers of the less developed to developing countries in making policies to attract more FDI inflows generally and in the textile industry.
Keywords: foreign direct investment (FDI); labor productivity; labor cost; ordinary least square (OLS); textile industry